The role of human resource management in risk management and recruitment process of a second-generation bank of Bangladesh - Simanto, Mir Shakrul Alam (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.